KARAKTERISTIK BIO-OIL DARI RUMPUT GELAGAH (Saccharum spontaneum Linn.) MENGGUNAKAN PROSES PIROLISIS CEPAT - Santiyo Wibowo; Djeni Hendra (BRIN Publishing, 2015)
T the information on production technology of bio-o his paper studies il from gelagah grass (Saccharum spontaneum L inn.) and its properties using fast pyrolysis. The variables used in this study are temperature 550 °C and 600 °C and size of samples which are 20, 40 and 60 mesh. The results showed that highest production of bio-oil attained from sample size 40 mesh with treatment at 550 °C, with the following characteristics; yields of liquid was 30 88%, phenol 7.58, pH 2.62, specific gravity 1.1108 g/ cm , heating value 25 29 MJ/ k g and flame power was at slow level. Bio-oil 3 produced by this process predominantly composed of acetic acid, phenols and dan 1-hydroxy 2-propanone.